Aqueous resin composition for lithium ion secondary battery separator, slurry for functional layer of lithium ion secondary battery separator, and lithium ion secondary battery separator
By using an aqueous resin composition with a specific particle size organic particles and an aqueous medium, a slurry for functional layers is formed, and complex problems in the prior art are solved, and excellent adhesion and resistance of lithium-ion secondary battery spacers are achieved. Heat shrinkability.
Patent Information
- Application Number
- CN202380037222.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-05-18
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art has complicated procedures when forming the adhesive layer and the porous film layer of the lithium-ion secondary battery spacer, and it is difficult to achieve excellent adhesion and heat shrinkage resistance in one coating.
Using an aqueous resin composition containing organic particles with a specific particle size and an aqueous medium, organic particles are prepared by suspension polymerization, and mixed with the aqueous medium to form a slurry for functional layer, and an excellent spacer is formed by a single coating.
Excellent adhesion to the electrode and heat shrinkage resistance are achieved, and the operation process is simplified, and it is suitable for spacers for lithium-ion secondary batteries.
Smart Images

Figure BDA0005107348480000131 
Figure BDA0005107348480000141
Abstract
Description
Technical Field
[0001] The present invention relates to an aqueous resin composition for a lithium ion secondary battery separator, a slurry for a functional layer, and a separator for a lithium ion secondary battery. Background Art
[0002] In recent years, battery components such as adhesive layers for the purpose of improving the adhesion between battery components and porous film layers for the purpose of improving heat resistance and strength, etc. have been used in secondary batteries. Specifically, an electrode formed by further forming an adhesive layer and / or a porous film layer on an electrode substrate formed by arranging an electrode composite material layer on a collector and a separator formed by forming an adhesive layer and / or a porous film layer on a separator substrate are used as battery components. In addition, the adhesive layer and porous film layer are usually formed in the following manner: a slurry-like adhesive layer containing a component, a bonding material component, and a dispersion medium such as water for exerting a desired function or a porous film layer slurry composition is supplied to an electrode substrate or a separator substrate and dried.
[0003] Therefore, in recent years, in order to achieve further improvement of secondary battery performance, attempts are being made to improve the adhesive layer and porous film layer arranged on the substrate (for example, with reference to patent document 1). The document discloses a technology in which a bonding material is used to form an adhesive layer for lithium ion secondary batteries, and the bonding material includes a particle-shaped polymer and an acrylic polymer having a core-shell structure of a shell portion with a core portion and a shell portion partially covering the outer surface of the core portion. In addition, a technology in which aluminum oxide and a bonding material containing an acrylic polymer are used to form a porous film for lithium ion secondary batteries is disclosed. In addition, by arranging the above-mentioned porous film on a spacer substrate, and further arranging the above-mentioned bonding layer on the porous film layer, the adhesion between the electrode and the spacer in the electrolyte can be improved, and the manufacture of a lithium ion secondary battery with excellent low temperature output characteristics and high temperature cycle characteristics is realized.
[0004] However, the method of forming such an adhesive layer and a porous membrane layer on a separator makes the operation process complicated, and thus simplification is required.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2015 / 064411 Summary of the invention
[0008] Problems to be solved by the invention
[0009] The problem to be solved by the present invention is to provide an aqueous resin composition for a lithium ion secondary battery separator, which can obtain a separator having excellent adhesion to an electrode and heat shrinkage resistance by a single application.
[0010] Means for solving problems
[0011] The present inventors have conducted extensive studies to solve the above problems and have found that the above problems can be solved by using an aqueous resin composition containing organic particles having a specific particle size and an aqueous medium, thereby completing the present invention.
[0012] That is, the present invention relates to an aqueous resin composition for a lithium ion secondary battery separator, characterized in that it contains organic particles (A) and an aqueous medium (B), wherein the volume average particle size of the organic particles (A) is 6 to 20 μm.
[0013] Effects of the Invention
[0014] By applying the functional layer slurry containing the aqueous resin composition for lithium ion secondary battery separator of the present invention to a separator, a separator having excellent adhesion to electrodes and heat shrinkage resistance can be obtained, and thus the separator can be suitably used for a lithium ion secondary battery separator. DETAILED DESCRIPTION
[0015] The aqueous resin composition for lithium ion secondary battery separators of the present invention contains organic particles (A) and an aqueous medium (B), and the volume average particle size of the organic particles (A) is 6 to 20 μm.
[0016] First, the organic particles (A) are described. The volume average particle size of the organic particles (A) is 6 to 20 μm. When the volume average particle size is 6 μm or more, the adhesion between the obtained porous membrane layer and the separator and the electrode becomes excellent, and when the volume average particle size is 20 μm or less, the dispersion stability becomes excellent. It should be noted that, from the perspective of further improving the dispersion stability, the volume average particle size of the organic particles (A) is preferably 6 to 15 μm.
[0017] In addition, from the viewpoint of further improving the adhesion between the electrode and the separator, the CV value of the organic particles (A) is preferably 0 to 80%.
[0018] The glass transition temperature of the organic particles (A) is preferably 10 to 110° C. If the glass transition temperature is 10° C. or higher, the particles are less likely to stick when wound on a separator roll, and the handling properties are improved. If the glass transition temperature is 110° C. or lower, the adhesion between the electrode and the separator is further improved.
[0019] The swelling ratio of the organic particles (A) in a mixed solvent (ethylene carbonate / ethyl methyl carbonate / diethyl carbonate = 40 / 20 / 40 (volume ratio at 25° C.)) used as an electrolyte is preferably 300% or less, more preferably 150% or less.
[0020] The gel fraction of the organic particles (A) in the mixed solvent is preferably 90% or more, more preferably 95% or more.
[0021] Examples of the organic component forming the organic particles (A) include resins such as acrylic resins, epoxy resins, urethane resins, and polyester resins, and acrylic resins are preferred.
[0022] The acrylic resin can be obtained by radical polymerization of monomer raw materials such as acrylic monomers and vinyl monomers.
[0023] Examples of the monomer include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate; monomers having a carboxyl group such as unsaturated monocarboxylic acids such as (meth)acrylic acid and crotonic acid, and unsaturated dicarboxylic acids such as maleic anhydride, maleic acid, itaconic anhydride, itaconic acid, and fumaric acid; 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxy-n-butyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, Monomers having hydroxyl groups, such as esters, 2-hydroxy-n-butyl (meth)acrylate, 3-hydroxy-n-butyl (meth)acrylate, 1,4-cyclohexanedimethanol mono(meth)acrylate, N-(2-hydroxyethyl) (meth)acrylamide, glycerol mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxyethyl phthalate, and lactone-modified (meth)acrylates having hydroxyl groups at the ends; N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, N , N-dimethylaminopropyl, (meth)acrylate N,N-diethylaminopropyl (meth)acrylate and other (meth)acrylates having an amino group, (meth)acrylamide, N-hydroxymethyl (meth)acrylamide and other monomers having an N-hydroxymethylamide group, N-butoxymethylacrylamide and other monomers having an N-alkoxymethylamide group, etc.; (meth)acrylates having a glycidyl group such as (meth)acrylate; polyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, polybutylene glycol (meth)acrylate, methoxypolybutylene glycol (meth)acrylate Polyalkylene glycol (meth)acrylates such as esters; vinyl monomers such as styrene, α-methylstyrene, p-methylstyrene, chloromethylstyrene, vinyl acetate, (meth)acrylonitrile; tetrahydrofurfuryl (meth)acrylate, benzyl (meth)acrylate; monomers having alkoxysilyl groups such as vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane; di(meth)acrylate monomers such as ethylene glycol di(meth)acrylate and propylene glycol di(meth)acrylate, etc. It should be noted that these monomers can be used alone or in combination of two or more.
[0024] As the monomer, a crosslinking monomer such as an alkoxysilyl group-containing monomer or a di(meth)acrylate monomer is preferably used in order to further improve the swelling ratio and gel fraction of the organic particles (A) in the mixed solvent.
[0025] The crosslinkable monomer in the monomer raw material is preferably 0.1 to 20% by mass. If it is 0.1% by mass or more, the swelling rate and gel fraction in the mixed solvent are further improved. If it is 20% by mass or less, the adhesion between the electrode and the separator is further improved.
[0026] It should be noted that in the present invention, "(meth)acrylic acid" refers to one or both of acrylic acid and methacrylic acid, "(meth)acryloyl" refers to one or both of acryloyl and methacryloyl, and "(meth)acrylate" refers to one or both of acrylate and methacrylate.
[0027] As a method for producing the organic particles (A) having a volume average particle size of 6 to 20 μm, various methods can be mentioned, and a suspension polymerization method is preferred because the organic particles (A) can be obtained by a simple operation without using any special additives.
[0028] As for the method of obtaining the acrylic resin particles as the above-mentioned organic particles (A) by the above-mentioned suspension polymerization method, for example, the following method can be cited: a mixed solution formed by a polymerizable monomer component containing the above-mentioned monomer raw material and a polymerization initiator, and an aqueous solution containing a surfactant having a critical micelle concentration (the minimum concentration at which the surfactant forms micelles in an aqueous solution) or more is stirred to prepare an emulsion, an aqueous solution containing a dispersion stabilizer is added to the emulsion so that the concentration of the surfactant is lower than the critical micelle concentration, and free radical polymerization is carried out at a temperature of 50 to 100°C.
[0029] Examples of the polymerization initiator include azo compounds such as 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), and azobiscyanovaleric acid; organic peroxides such as tert-butyl peroxypivalate, tert-butyl peroxybenzoate, tert-butyl peroxy-2-ethylhexanoate, di-tert-butyl peroxide, cumene hydroperoxide, benzoyl peroxide, and tert-butyl hydroperoxide; and inorganic peroxides such as hydrogen peroxide, ammonium persulfate, potassium persulfate, and sodium persulfate. It should be noted that these polymerization initiators may be used alone or in combination of two or more.
[0030] As the above-mentioned aqueous medium (B), water, organic solvents miscible with water, and mixtures thereof can be cited. As organic solvents miscible with water, for example, alcohols such as methanol, ethanol, n-propanol and isopropanol; ketones such as acetone and methyl ethyl ketone; polyalkylene glycols such as ethylene glycol, diethylene glycol, propylene glycol; alkyl ethers of polyalkylene glycols; lactams such as N-methyl-2-pyrrolidone, etc. can be cited. In the present invention, only water can be used, and a mixture of water and an organic solvent miscible with water can also be used, or only an organic solvent miscible with water can also be used. From the aspects of safety and environmental load, it is preferred to use only water, or a mixture of water and an organic solvent miscible with water, and it is particularly preferred to use only water.
[0031] As the aqueous medium (B), it is convenient and preferable to use the aqueous medium used when producing the organic particles (A) by a suspension polymerization method as it is.
[0032] As the above-mentioned emulsifier, for example, anionic emulsifiers such as sulfuric acid esters of higher alcohols and salts thereof, alkylbenzene sulfonates, polyoxyethylene alkylbenzene sulfonates, polyoxyethylene alkyldiphenyl ether sulfonates, sulfuric acid half-ester salts of polyoxyethylene alkyl ethers, alkyldiphenyl ether disulfonates, and dialkyl succinate sulfonates can be cited; nonionic emulsifiers such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene diphenyl ethers, polyoxyethylene-polyoxypropylene block copolymers, and acetylene glycol systems; cationic emulsifiers such as alkylammonium salts; zwitterionic emulsifiers such as alkyl (amide) betaines and alkyl dimethyl amine oxides, etc. It should be noted that these emulsifiers can be used alone or in combination of two or more. In addition, these emulsifiers are above the critical micelle concentration, preferably 0.1 to 10 times the critical micelle concentration.
[0033] Regarding the stirring of the mixed solution formed by the polymerizable monomer component containing the above-mentioned acrylic monomer and polymerization initiator, and the aqueous solution containing a surfactant, it is particularly preferred to stir while applying shear, for example, a stirring device such as a homomixer, a high-pressure homogenizer, an ultrasonic dispersing device, a high-pressure jet-type dispersing device, a static mixer, etc. can be used. By stirring while applying shear, an emulsion with a volume average particle size of 6 to 20 μm can be easily prepared.
[0034] An aqueous solution containing a dispersion stabilizer is added to the emulsion obtained as described above to prepare a dispersion in which the concentration of the surfactant in the emulsion is greater than 0.01 and less than 1.0 of the critical concentration, and then suspension polymerization is performed to obtain the above-mentioned organic particles having a volume average particle size of 6 to 20 μm.
[0035] Examples of the dispersion stabilizer include water-soluble resins such as polyvinyl alcohol, polyvinyl pyrrolidone, methyl cellulose, and hydroxyethyl cellulose. These dispersion stabilizers may be used alone or in combination of two or more.
[0036] The aqueous resin composition for lithium ion secondary battery separators of the present invention contains the organic particles (A) and an aqueous medium (B), and the resin particles (A) obtained by the suspension polymerization method are preferably dispersed in the aqueous medium (B).
[0037] Furthermore, the amount of the organic solvent in the aqueous resin composition of the present invention can be reduced by subjecting the composition to a desolvation step as necessary.
[0038] The aqueous resin composition of the present invention obtained by the above method preferably contains 5 to 60% by mass of the organic particles (A), more preferably 10 to 50% by mass, based on the total amount of the aqueous resin composition, from the viewpoint of further improving coating workability.
[0039] The aqueous resin composition of the present invention preferably contains 95 to 40% by mass, more preferably 90 to 50% by mass of the aqueous medium (B) based on the total amount of the aqueous resin composition in order to further improve coating workability.
[0040] The aqueous resin composition of the present invention may contain a water-soluble polymerization inhibitor such as sodium nitrite or hydroquinone as required.
[0041] In addition, as needed, the aqueous resin composition of the present invention can also be used in combination with additives such as a curing agent, a curing catalyst, a lubricant, a filler, a thixotropic agent, a tackifier, a wax, a heat stabilizer, a light stabilizer, a fluorescent whitening agent, a foaming agent, a pH adjuster, a leveling agent, an anti-gelling agent, a dispersion stabilizer, an antioxidant, a free radical scavenger, a heat resistance imparting agent, an inorganic filler, an organic filler, a plasticizer, a reinforcing agent, a catalyst, an antibacterial agent, an antifungal agent, an antirust agent, a thermoplastic resin, a thermosetting resin, a pigment, a dye, an electrical conductivity imparting agent, an antistatic agent, a moisture permeability enhancing agent, a water repellent, an oil repellent, a hollow foam, a compound containing crystal water, a flame retardant, a water absorbent, a moisture absorbent, a deodorant, a foam stabilizer, a defoamer, an antifungal agent, a preservative, an antialgae agent, a pigment dispersant, an anti-blocking agent, an anti-hydrolysis agent, and a pigment.
[0042] The slurry for the functional layer of the lithium ion secondary battery separator of the present invention contains the aqueous resin composition of the present invention, non-conductive particles and a water-soluble polymer. In the slurry for the functional layer, the organic particles (A) in the aqueous resin composition are preferably contained at 0.1 to 100% by mass, and the water-soluble polymer is contained at 0.1 to 100% by mass, relative to 100 parts by mass of the non-conductive particles.
[0043] As the non-conductive particles, for example, inorganic particles and organic particles can be used, and inorganic particles are preferred.
[0044] As the above-mentioned inorganic particles, for example, oxide particles such as aluminum oxide (alumina), silicon oxide, magnesium oxide, titanium oxide, BaTiO2, ZrO, aluminum oxide-silicon dioxide composite oxide, nitride particles such as aluminum nitride, boron nitride, covalent bond crystal particles such as silicon, diamond, insoluble ionic crystal particles such as barium sulfate, calcium fluoride, barium fluoride, talc, clay particles such as montmorillonite, etc. can be cited. Among these, aluminum oxide (alumina) is preferred. It should be noted that these inorganic particles can be used alone or in combination of two or more.
[0045] In addition, as the above-mentioned organic particles, for example, polyethylene, polystyrene, polydivinylbenzene, styrene-divinylbenzene copolymer crosslinked products, and various crosslinked polymer particles such as polyimide, polyamide, polyamide-imide, melamine resin, phenol resin, benzoguanamine-formaldehyde condensate, polysulfone, polyacrylonitrile, polyaramide, polyacetal, thermoplastic polyimide, etc. can be cited. It should be noted that these organic particles can be used alone or in combination of two or more.
[0046] As the water-soluble polymer, for example, cellulose polymers such as carboxymethyl cellulose, methyl cellulose, hydroxypropyl cellulose, and their ammonium salts and alkali metal salts; poly(meth)acrylic acid and its ammonium salt and alkali metal salt; polyvinyl alcohol compounds such as polyvinyl alcohol, copolymers of acrylic acid or acrylic acid salt and vinyl alcohol, maleic anhydride or maleic acid or fumaric acid and vinyl alcohol; polyethylene glycol, polyethylene oxide, polyvinyl pyrrolidone, modified polyacrylic acid, oxidized starch, starch phosphate, casein, various modified starches, etc. It should be noted that these water-soluble polymers can be used alone or in combination of two or more.
[0047] Examples of the particulate polymer include cross-linked poly(meth)acrylic acid particles, cross-linked poly(meth)acrylate particles, cross-linked polystyrene particles, cross-linked resin particles of (meth)acrylate and styrene, melamine resin particles, nylon particles, polyimide particles, polyamide-imide particles, phenol resin particles, polytetrafluoroethylene particles, fluorine resin particles, silicone resin particles, etc. It should be noted that these particulate polymers may be used alone or in combination of two or more.
[0048] The functional layer in the present invention can be formed by applying the above-mentioned functional layer slurry to the spacer. As a method for applying the above-mentioned functional layer slurry composition on the substrate, it is not particularly limited, and a known method can be used. Specifically, as a coating method, a scraper method, an immersion method, a reverse roller method, a direct roller method, a gravure method, an extrusion method, a brush coating method, etc. can be used. At this time, the functional layer slurry composition can be applied only to a single side of the substrate, or it can be applied to both sides.
[0049] The method for drying the functional layer slurry composition on the substrate is not particularly limited, and a known method can be used, for example, a drying method using warm air, hot air, low-humidity air, a vacuum drying method, a drying method using irradiation of infrared rays, electron beams, etc. By drying the functional layer slurry composition on the substrate in this way, a spacer of the present invention having a functional layer formed on the substrate can be obtained.
[0050] The adhesion between the separator of the present invention and the electrode material is preferably 10 N / m or more.
[0051] Furthermore, the heat shrinkage rate of the separator of the present invention is preferably 5% or less.
[0052] Example
[0053] Hereinafter, the present invention will be described in more detail with reference to specific examples.
[0054] The particle size of the organic particles was measured using a laser diffraction method. Specifically, an aqueous dispersion containing organic particles (solid content concentration 25% by mass) was used as a sample, and in the particle size distribution (volume basis) obtained by a laser diffraction particle size distribution measuring device (manufactured by Malvern Panalytical, "Mastersizer 2000"), the particle size at which the cumulative volume calculated from the smaller diameter side becomes 50% was obtained and used as the volume average particle size (μm).
[0055] Regarding the gel fraction of organic particles with respect to the electrolyte, a film with a thickness of 300 μm is prepared by drying an aqueous dispersion of organic particles at 108°C for 4 hours to remove water. Accurately weigh about 1 g of the membrane, and set the mass of the membrane to W0. The membrane is immersed in about 100 g of a mixed solvent (EC / MEC / DEC (volume mixing ratio at 25°C) = 40 / 20 / 40) at 60°C for 72 hours. Thereafter, the membrane is scooped up from the mixed solvent. Wipe off the mixed solvent of the scooped membrane with a towel, then vacuum dry it at 108°C for 4 hours, and measure its mass (mass of the insoluble component) W1. Then, the gel fraction (%) of the organic particles with respect to the mixed solvent is calculated according to the following formula.
[0056] Gel fraction for mixed solvent (%) = (W1 / W0) × 100
[0057] Regarding the swelling rate of organic particles in the electrolyte, a film with a thickness of 300 μm was prepared by drying an aqueous dispersion of organic particles at 108°C for 4 hours to remove water. About 1 g of the membrane was accurately weighed, and the mass of the membrane was set as W0. The membrane was immersed in about 100 g of a mixed solvent (EC / MEC / DEC (volume mixing ratio at 25°C) = 40 / 20 / 40) at 60°C for 72 hours. Thereafter, the membrane was scooped up from the mixed solvent. The mixed solvent of the scooped membrane was wiped off with a towel, and its mass W1 was measured. Then, the swelling rate (%) of the organic particles in the mixed solvent was calculated according to the following formula.
[0058] Swelling ratio for mixed solvent (%) = (W1 / W0) × 100 - 100
[0059] Regarding the calculation method of the glass transition temperature (Tg), 10 mg of the measurement sample was weighed in an aluminum pan, and the DSC curve was measured at room temperature and humidity in the measurement temperature range of -100°C to 500°C at a heating rate of 10°C / min using a differential thermal analysis measuring apparatus ("QA-100" manufactured by TA Instruments) and an empty aluminum pan as a reference. The intersection of the baseline before the endothermic peak of the DSC curve where the differential signal (DDSC) becomes 0.05 mW / min / mg or more and the tangent of the DSC curve at the inflection point that first appears after the endothermic peak is determined as the glass transition temperature (Tg).
[0060] (Example 1: Synthesis of aqueous resin composition (1))
[0061] 1.00 g of tert-butyl peroxyoctanoate was dissolved in a mixed solution formed by 121.4 g of styrene, 76.2 g of 2-ethylhexyl acrylate, and 2.4 g of 3-methacryloyloxypropyltrimethoxysilane as a polymerizable monomer component. Separately, 3.00 g of alkylbenzene sulfonate ("NEOGEN S-20F" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was dissolved in 200.0 g of water. The above-mentioned polymerizable monomer components were mixed in the aqueous solution, and stirred at a speed of 6000 rpm for 10 minutes using TK Homomixer (manufactured by Tokushiki Kagaku Kogyo Co., Ltd.). The obtained emulsion was placed in a 2L reaction container with a stirrer and a thermometer, and an aqueous solution obtained by dissolving 8.0 g of polyvinyl alcohol ("44-88" manufactured by KURARAY Co., Ltd.) in 430.7 g of water was further added, and polymerization was carried out at 75°C for 5 hours while stirring in a nitrogen stream. Thereafter, the temperature was raised to 85°C and polymerization was performed for 2 hours to obtain an aqueous resin composition (1). The volume average particle size of the organic particles (A-1) in the aqueous resin composition (1) was 7.2 μm.
[0062] (Example 2: Synthesis of aqueous resin composition (2))
[0063] A water-based resin composition (2) was obtained in the same manner as in Example 1 except that the rotation speed of the TK Homomixer was changed to 3500 rpm. The volume average particle size of the organic particles (A-2) in the water-based resin composition (2) was 9.5 μm.
[0064] (Example 3: Synthesis of aqueous resin composition (3))
[0065] In a mixed solution of 140.5 g of styrene, 57.1 g of 2-ethylhexyl acrylate, and 2.4 g of 3-methacryloxypropyltrimethoxysilane, 1.00 g of tert-butyl peroxyoctanoate was dissolved as a polymerizable monomer component, and an aqueous resin composition (3) was obtained in the same manner as in Example 1 except for the above. The volume average particle size of the organic particles (A-3) in the aqueous resin composition (3) was 6.8 μm.
[0066] (Example 4: Synthesis of aqueous resin composition (4))
[0067] In a mixed solution of 121.4 g of methyl methacrylate, 76.2 g of 2-ethylhexyl acrylate, and 2.4 g of 3-methacryloxypropyltrimethoxysilane, 1.00 g of tert-butyl peroxyoctanoate was dissolved as a polymerizable monomer component, and an aqueous resin composition (4) was obtained in the same manner as in Example 1 except that the above was used. The volume average particle size of the organic particles (A-4) in the aqueous resin composition (4) was 7.0 μm.
[0068] (Example 5: Synthesis of Aqueous Resin Composition (5))
[0069] In a mixed solution of 121.4 g of styrene, 76.2 g of 2-ethylhexyl acrylate, and 2.4 g of ethylene glycol dimethacrylate, 1.00 g of t-butyl peroxyoctanoate was dissolved as a polymerizable monomer component, and an aqueous resin composition (5) was obtained in the same manner as in Example 1 except for the above. The volume average particle size of the organic particles (A-5) in the aqueous resin composition (5) was 6.2 μm.
[0070] (Comparative Example 1: Synthesis of Aqueous Resin Composition (R1))
[0071] A water-based resin composition (R1) was obtained in the same manner as in Example 1 except that the rotation speed of the TK Homomixer was changed to 10000 rpm. The volume average particle size of the organic particles (RA-1) in the water-based resin composition (R1) was 1.9 μm.
[0072] (Comparative Example 2: Synthesis of Aqueous Resin Composition (R2))
[0073] 1.00 g of tert-butyl peroxyoctanoate was dissolved in a mixed solution formed by 121.4 g of styrene and 76.2 g of 2-ethylhexyl acrylate as a polymerizable monomer component. Separately, 3.00 g of alkylbenzene sulfonate ("NEOGEN S-20F" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was dissolved in 200.0 g of water. The above-mentioned polymerizable monomer components were mixed in the aqueous solution, and stirred at a speed of 8000 rpm for 10 minutes using TK Homomixer (manufactured by Tokushiki Kagaku Kogyo Co., Ltd.). The obtained emulsion was loaded into a 2L reaction container with a stirrer and a thermometer, and an aqueous solution obtained by dissolving 8.0 g of polyvinyl alcohol ("44-88" manufactured by KURARAY Co., Ltd.) in 430.7 g of water was further added, and polymerization was carried out at 75°C for 5 hours while stirring in a nitrogen stream. Thereafter, the temperature was raised to 85°C, and polymerization was carried out for 2 hours to obtain an aqueous resin composition (R2). The volume average particle size of the organic particles (A-1) in the aqueous resin composition (R2) was 3.2 μm.
[0074] (Comparative Example 3: Synthesis of Aqueous Resin Composition (R3))
[0075] Into a reactor equipped with a stirrer and a thermometer, 70 g of ion exchange water, 0.15 g of sodium lauryl sulfate ("EMAL 2F" manufactured by Kao Chemical Co., Ltd.) as an emulsifier, and 0.5 g of ammonium persulfate as a polymerization initiator were respectively supplied, the gas phase was replaced with nitrogen, and the temperature was raised to 60°C.
[0076] On the other hand, 50 g of ion exchange water, 0.5 g of sodium dodecylbenzene sulfonate as an emulsifier, 94 g of butyl acrylate as a polymerizable monomer, 2 g of acrylonitrile, 2 g of methacrylic acid, 1 g of N-hydroxymethyl acrylamide and 1 g of allyl glycidyl ether are supplied to another container and mixed to obtain a monomer mixture. The monomer mixture is continuously added to the above-mentioned reactor for 4 hours to perform polymerization. It should be noted that during the addition of the monomer mixture, the polymerization reaction is continued at a temperature of 60°C. After the addition is completed, the mixture is further stirred at a temperature of 70°C for 3 hours to terminate the polymerization reaction and obtain an aqueous resin composition (R3). The volume average particle size of the organic particles (RA-3) in the aqueous resin composition (R3) is 0.3 μm.
[0077] [Preparation of slurry for functional layer]
[0078] In a mixed solution of 30.0 parts by mass of polyvinyl alcohol (DIC Corporation "DICNAL VA-29") and 0.36 parts by mass of a dispersant (Tetsutani Corporation "BYK-154"), 30.0 parts by mass of alumina (Sumitomo Chemical Co., Ltd. "AKP-3000") was slowly added while stirring at 000 rpm with a homogenizer, and dispersed for 5 minutes. After becoming uniform, 6.0 parts by mass of the aqueous resin composition obtained above and 15.8 parts by mass of ion exchange water were added, and dispersed at 5000 rpm for 10 minutes with a homogenizer. The obtained slurry was filtered with a 100-mesh metal mesh to obtain a functional layer slurry.
[0079] [Manufacturing of spacers]
[0080] The functional layer slurry was applied to a polyethylene separator substrate having a thickness of 12 μm using a coating bar so that the dry film thickness became 4 μm, thereby obtaining a separator having a functional layer. The drying temperature was 80° C. and the drying time was 1 minute.
[0081] [Evaluation of Adhesion]
[0082] The peel strength was measured as follows to evaluate the adhesion. Specifically, the composite material layer of the negative electrode (manufactured by Hohsen Co., Ltd., HS-LIB-N-Gr-001) was made to face the functional layer on the separator, and the negative electrode and the separator were pressed for 1 minute at a load of 6.5 MPa at a temperature of 80°C, thereby making a test sample in which the negative electrode and the separator were bonded. It was cut into a width of 20 mm and a height of 120 mm, and after a double-sided tape was attached to the surface of the negative electrode, it was fixed to a metal plate with a double-sided tape.
[0083] The stress when one end of the test piece on the separator side is pulled and peeled off in the vertical direction at a rate of 10 mm / sec is measured. A larger value of the peel strength with the electrode is more preferable.
[0084] Machine used: Shimadzu Autograph AG-10KNX Plus
[0085] Use fixture: tensile chuck
[0086] Test speed: 100mm / min
[0087] Use unit: 50N
[0088] Measuring temperature: room temperature
[0089] [Evaluation of Heat Shrinkage Resistance]
[0090] Cut the spacer coated with the functional layer into 5 cm squares, sandwich the test piece between thick paper, and heat it in a dryer with an internal temperature of 150°C for 1 hour before taking it out. Measure the distance between the midpoints of the two opposite sides and use it as the size after shrinkage (mm). Using the obtained initial size and the size after shrinkage, calculate the length in the MD direction (long dimension direction) and the length in the TD direction (transverse direction) by the following calculation formula, and obtain the heat shrinkage rate (%) based on the average value. The smaller the value of the heat shrinkage rate, the better.
[0091] Thermal shrinkage (%) = {initial size (mm) - size after shrinkage (mm)} / initial size (mm) × 100
[0092] Tables 1 and 2 show the evaluation results of Examples 1 to 5 and Comparative Examples 1 to 3.
[0093] [Table 1]
[0094]
[0095] [Table 2]
[0096]
[0097] It was confirmed that the separators coated with the compositions of Examples 1 to 5, which are the aqueous resin compositions of the present invention, were excellent in adhesion to the electrodes and heat shrinkage resistance.
[0098] On the other hand, Comparative Examples 1 to 3 are examples in which the volume average particle size of the organic particles (A) is smaller than the lower limit of the present invention, and it was confirmed that the adhesion to the electrode was insufficient.
Claims
1. A water-based resin composition for a lithium-ion secondary battery separator, characterized in that: Contains organic particles (A) and an aqueous medium (B), wherein the volume average particle size of the organic particles (A) is 6 μm to 20 μm.
2. The aqueous resin composition for lithium ion secondary battery separator according to claim 1, wherein The organic particles (A) have a swelling ratio of 300% or less and a gel fraction of 90% or more with respect to a mixed solvent, wherein the mixed solvent is a mixed solvent of ethylene carbonate / ethyl methyl carbonate / diethyl carbonate=40 / 20 / 40 in volume ratio at 25°C.
3. The aqueous resin composition for lithium ion secondary battery separator according to claim 1, wherein The volume ratio of particles having a particle size of 2 μm or less in the organic particles (A) is 30% or less. 4 . The aqueous resin composition for a lithium ion secondary battery separator according to claim 1 , comprising 0.1% by mass to 20% by mass of a dispersion stabilizer (C). 5 . A slurry for a lithium ion secondary battery separator functional layer, comprising the aqueous resin composition for a lithium ion secondary battery separator according to claim 1 . 6 . A separator for a lithium ion secondary battery, comprising a coating film obtained by using the slurry for a lithium ion secondary battery separator functional layer according to claim 5 .
Citation Information
Patent Citations
Particulate polymer for use in binder for lithium-ion secondary battery; adhesive layer; and porous-membrane composition
WO2015064411A1